A GEOMETRICAL ROBUST IMAGE DATA HIDING SCHEME BASED ON CONTOURLET TRANSFORM - M. Duc, Duong; A. Duc, Duong (Vietnam Journal of Science and Technology, 2012)
ABSTRACT In this paper, we present a new approach for data hiding in digital images by using multiple embedded stages. The new scheme involves feature point detector that orient for a novel Contourlet transform-hiding algorithm. By this way,our model can withstand geometric, desynchronization attacks and other common attacks with a high capacity. The resulting watermarking scheme is suitable for public watermarking applications, where the original image is not available for watermark extraction. Experimental results demonstrate that our proposed technique is robust to a wide range of attacks. Keywords. data hiding, geometrical attacks, watermarking Contourlet transform,